HUBUNGAN PENGGUNAAN ALAT KONTRASEPSI SUNTIK DENGAN SIKLUS MENSTRUASI PADA AKSEPTOR KB SUNTIK YANG PERIKSA DI POLINDES MAYANG - Tunjung Sri Yulianti; Apresia Murtati; Ratna Dwi Maryanti (KOSALA : Jurnal Ilmu Kesehatan, 2015)
AbstractIntroduction: Indonesia is the world's 5th State with estimated population, namely 249 million. With fertility rates or Total Fertility Rate (TFR) 2.6, Indonesia was still above the average TFR ASEAN countries namely 2.4. The Agency's data on population and family planning (BKKBN) National shows that by 2013 there 8.500.247 (Fertile Age Couples) who are participants in a new and almost KB half 4.128.115 (48,56) using a method of contraception injections. (Department of health, 2013) Almost all contraceptives have side effects. At a time when researchers conduct interviews beginning on the check Acceptor in Polindes Mayang, Gatak, Sukoharjo, most mothers who use contraception injections said that their menstrual cycles become irregular.The purpose: To know the relation of the use of contraception injections with menstrual cycle on the Acceptor KB in Polindes Mayang.The method: The research design with analytic research, with correlation test statistic Chi Squared or XÂ² with p value of 0.05.The results: There is a relationship between the use of contraception injections with menstrual cycle on the Acceptor KB in Polindes Mayang with Pearson Chi Square value of 0.001 p (probability 0.05) the magnitude of the relationship 0,536 or 53,6 %.Conclusion: There is a relationship between the use of contraception injections with menstrual cycle on the Acceptor KB in Polindes Mayang.Keywords: contraception injections, menstrual cycle